The Influence of Fiscal Policy and Monetary Policy on Economic Growth in Indonesia - Suyanto; Denpharanto Agung Krisprimandoyo; Pontjo Bambang Mahargiono (Global Writing Academica Researching & Publishing, 2023)
The purpose of this study is to investigate how changes in fiscal policy and monetary policy have impacted economic expansion in Indonesia. Spending by the government, tax rates, the rate at which banks open new accounts, and the total amount of money in circulation are the variables that were investigated in this study. This study takes a quantitative approach, and the analytical method that is employed is multiple linear regression using secondary data on economic growth from 2013-2022. The data for this study was collected from the United States Department of Commerce. The study's conclusions indicate that taxes and the amount of money in circulation impact Indonesia's economic growth, but neither government spending nor interest rates on BI deposits do. Additionally, how government expenditure, taxes, interest rates, and the amount of money in circulation affect economic growth. It is 99.66%. As a result, while making future decisions about the economy, the government will need to take into account both kinds of policies in a comprehensive manner.